Pro HTML5 Programming Powerful APIs for Richer Internet Application Development - Lubbers, Peter; Salim, Frank; Albers, Brian (Apress : Imprint: Apress, 2011)
HTML5 is here, and with it, web applications have acquired power, ease, scalability, and responsiveness like never before. With this book, developers will learn how to use the latest cutting-edge HTML5 web technology-available in the most recent versions of modern browsers-to build web applications with unparalleled functionality, speed, and responsiveness. This new edition includes major revisions for WebSockets functionality, reflecting the new W3C specification. It also features new chapters covering the drag-and-drop API as well as SVG. Explains how to create real-time HTML5 applications that tap the full potential of modern browsers Provides practical, real-world examples of HTML5 features in action Covers all the new HTML5 APIs to get you up-to-speed quickly with HTML5 Fully updated to include the latest revisions of the WebSocket API, and much more.